2009
DOI: 10.1017/s095026880900209x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of screening broiler chicken flocks for risk markers as an aid for meat inspection

Abstract: The feasibility of using risk markers to screen broiler chicken flocks and anticipate their risk of condemnation at meat inspection was examined in 404 randomly selected flocks in 15 French slaughterhouses in 2005. Condemnation rate and information about rearing conditions, health history, catching and loading, transport and slaughtering were collected. The Poisson regression model of the condemnation rate consisted of six simple and biologically relevant predictors: production type, frequency of farmer's visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…If producers cull sick and disabled birds during rearing (Ansong-Danquah 1987) and catchers identify birds that are either not fit for transport or are too small for slaughter, there are fewer birds at risk of mortality during transport due to pre-existing conditions. Lupo et al (2009) found significant relationships between (a) the % DOA and the % of birds condemned after slaughter as not fit for human consumption due the presence of macroscopic abnormalities, and (b) the % mortality during rearing and the % of birds condemned F o r R e v i e w O n l y after slaughter, as not fit for human consumption. Broilers can be weakened during rearing due to infectious diseases causing pathophysiological changes and this can place them at a greater risk of mortality during transport (Nijdam et al 2006).…”
mentioning
confidence: 91%
“…If producers cull sick and disabled birds during rearing (Ansong-Danquah 1987) and catchers identify birds that are either not fit for transport or are too small for slaughter, there are fewer birds at risk of mortality during transport due to pre-existing conditions. Lupo et al (2009) found significant relationships between (a) the % DOA and the % of birds condemned after slaughter as not fit for human consumption due the presence of macroscopic abnormalities, and (b) the % mortality during rearing and the % of birds condemned F o r R e v i e w O n l y after slaughter, as not fit for human consumption. Broilers can be weakened during rearing due to infectious diseases causing pathophysiological changes and this can place them at a greater risk of mortality during transport (Nijdam et al 2006).…”
mentioning
confidence: 91%
“…It also indicates that the birds concerned might have experienced poor welfare, and dead on arrival (DoA) shall be recorded in the European Union according to Council Directive 2007/43/EC (2007. Moreover, it has recently been shown that DoAs are related to subsequent sanitary condemnation (Lupo et al, 2009). Both DoA and carcass rejection can result from all primary production steps (Lupo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has recently been shown that DoAs are related to subsequent sanitary condemnation (Lupo et al, 2009). Both DoA and carcass rejection can result from all primary production steps (Lupo et al, 2009). In an integrated 'from farm to fork' approach to food animal production, all these primary production steps should be considered as related to poultry production quality (Terlouw et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a national study of male turkeys at slaughter in France during 2006, the within-flock weighted average condemnation proportion was 1.8% (95% confidence interval, 1.3-2.3%; Lupo et al, 2010b). In a study of broilers slaughtered in France during 2005, a condemnation rate between 0.85 and 0.89% was observed (Lupo et al, 2009). …”
Section: Removal Of Visual Post-mortem Inspectionmentioning
confidence: 99%
“…Lupo and coworkers (Lupo et al, 2008(Lupo et al, , 2009(Lupo et al, , 2010a describe several studies investigating whether primary production information would predict the risk of condemnation. In a study of male turkey broilers, using data from 2006 from 117 flocks in 13 slaughterhouses located in Western France, three variables were found to be significantly associated with increased risk of condemnation: observed locomotor disorders on the farm, high cumulative mortality 2 weeks before slaughter, and clinical signs observed by the Veterinary Services during the ante-mortem inspection at the slaughterhouse (Lupo et al, 2010b).…”
Section: Incorporating Food Chain Informationmentioning
confidence: 99%